The Influence of Leadership on Communications, Job Satisfaction, and Oganization Commitment in Bangking Industry - Hidayat, Rachmad (Makara Human Behavior Studies in Asia, 2013)
The paper presents an analysis of the leadership effect, communication, and job satisfaction to organizational commitment in the banking firm. The Structural Equation Modeling (SEM) is used to analyze the causality pattern of the involved variables. In addition, to measure the influence among the variables defined, survey method is implemented. The population used was all staff of state and private banks in East Java Area with 200 respondents. The study result shows that the direct effect of leadership gives significant positive impact to the organizational communication and organizational commitment. On the other hand, there is no significance impact of the leadership to the job satisfaction. There is no effect of indirect, positive significance of leadership on organizational commitment with job satisfaction intervening. There is no direct influence, the positive significance of leadership on organizational commitment by intervening organizational communication and job satisfaction.